Case report: a robotic-vaginal approach for total vaginectomy and hysterectomy with pelvic sentinel lymph node dissection in primary vaginal melanoma: a 10-step technique and literature review - Van Trappen, Philippe; Lebbe, Ines; De Cuypere, Eveline; Claes, Nele (Frontiers in Surgery, 2023)
Introduction: Primary vaginal melanoma is extremely rare, has a poor prognosis and occurs mostly in elderly women. The diagnosis is based on histology and immunohistochemistry of a biopsy. Given the rarity of vaginal melanoma no standardized treatment guidelines are established, however, surgery is the primary treatment modality in the absence of metastatic disease. Most reports in the literature are retrospective single cases, case series and population based studies. The open surgical approach is the main modality reported. Here we report for the first time a 10-step combined robotic-vaginal technique, with en bloc resection of the uterus and total vagina, for clinically early-stage primary vaginal melanoma. In addition, the patient underwent a robotic pelvic bilateral sentinel lymph node dissection. The literature on the surgical approach for vaginal melanoma is reviewed. Case presentation: A 73-year old woman was referred to our tertiary cancer center and was clinically staged according to the 2009 International Federation of Gynaecology and Obstetrics (FIGO) staging for vaginal cancer as FIGO-stage I (cT1bN0M0), and according to the American Joint Committee on Cancer (AJCC) for (cutaneous) Melanoma Staging as clinical stage IB. Preoperative imaging with magnetic resonance imaging (MRI), FDG-positron emission tomography-computed tomography (PET-CT) and ultrasound of the groins did not reveal any adenopathy nor metastases. The patient was planned for a combined vaginal and robotic en bloc total vaginectomy and hysterectomy, as well as a pelvic bilateral sentinel lymph node dissection. Results: The surgical procedure was performed in 10 steps described here in the case report. The pathology revealed free surgical margins and all sentinel lymph nodes were negative. The postoperative recovery was uneventful, and the patient was discharged on day 5 postoperatively. Conclusion: The main surgical approach reported for primary early-stage vaginal melanoma is open surgery. A minimally invasive surgical approach, as described here combined vaginal-robotic, for the surgical treatment of early-stage vaginal melanoma enables precise dissection, low surgical morbidity and fast recovery for the patient.